Lack Of Synergy Between Government and Society During the Covid-19 Pandemic - Gunawan, Asep; D.A.R, Deni; Priyanto, Priyanto; Risman, Helda (Jurnal Multidisiplin Indonesia, 2023)
This article discusses the government's and society's unpreparedness in dealing with the Covid-19 pandemic. To overcome various limitations and challenges in handling the Covid-19 pandemic in Indonesia, it is necessary to realize cooperation by mobilizing all national resources and potential. The synergy between governments is also needed so that there are no overlapping regulations. The government's strictness in making rules and sanctions greatly influences handling the Covid-19 pandemic. The community is also asked to obey and believe in every policy made. So far, people have tended to ignore existing policies so that the spread of Covid-19 has become more massive and uncontrollable. Cooperation between government and society is needed in the current crisis conditions